Analysis Insurance Costs for Smokers Using Linear Regression - Hardayani, Bernadheta Dinar Koen; Widiantoro, Albertus Dwiyoga (SISFORMA, 2024)
This study explores the effect of smoking habits on insurance costs using the linear regression method. Data was collected from various sources that included information on smoking habits and insurance costs. Using RapidMiner, linear regression analysis was conducted to predict the pattern of insurance costs influenced by smoking status. The results show that smokers tend to pay higher insurance premiums than non-smokers, in line with the health risks they carry. This study highlights the importance of including smoking habits in insurance pricing models, which can help insurance companies set more appropriate premiums based on individual risk. Thus, the results of this study not only deepen the understanding of the relationship between smoking and insurance costs, but also provide practical guidance for insurance companies in developing pricing policies that are more responsive to customers' risk profiles.